Active learning improves financial education: Experimental evidence - Tim Kaiser; Lukas Menkhoff (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We conduct a randomized field experiment to study the effects of two financial education interventions offered to small-scale retailers in Uganda. The treatments contrast "active learning" with "traditional lecturing" within standardized lesson-plans. We find that active learning has a positive and economically meaningful impact on savings and investment outcomes, in contrast to insignificant impacts of lecturing. These results are not conditional on prior education or financial literacy. Tentative evidence suggests that only active learning stimulates several cognitive and non-cognitive mechanisms; moreover, a social mechanism may be at play as treated individuals join social groups discussing financial matters.
Keywords: I21; A20; D14; O16; 330; financial behavior; financial literacy; active learning; lecturing; training method; field experiment